(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
This research dealt with the study of the hydrogeomorphological harvest of the Wadi Raml Basin, which originates from the Mediterranean northwest of Tripoli to the Mediterranean Sea at a distance of (40 km), where the focus was on the morphometric gain of the basin, its drainage network, and the contributions of hydrogeology and its extent to protecting agricultural lands from some diverse problems such as floods, soil erosion, drought, and desertification. By saving a large amount of water that was wasted without results, he relied on the latest morphometric and hydrological equations that are used in such studies.